INTEGRATION OF GIS AND MULTI-CRITERIA HIERARCHICAL ANALYSIS FOR URBAN PLANNING SUPPORT: CASE OF THE WILAYA OF CONSTANTINE - Boussetti Sandra,; Yahia Amina, (International Journal of Innovative Technologies in Social Science, 2024)
Sustainable urban planning requires effective decision-making tools, especially in contexts of rapid development and increasing environmental pressures, as is the case in the wilaya of Constantine, Algeria. Integrating Geographic Information Systems (GIS) with Analytical Hierarchy Process (AHP) offers a robust methodology to support this decision-making process. This approach has proven useful in interpreting complex spatial issues. By identifying criteria aligned with targeted objectives and mapping geographic and attribute data at the Constantine wilaya scale, it was possible to prioritize identified indicators, quantitatively assess the phenomenon, and compare various development scenarios within the study areas. The study results indicated that, of the total area of 221,819 km², 55.17% (122,382 km²) of barren lands (suitable for habitability) are most suitable for urban development, 26.84% (59,550 km²) are moderately suitable for urban development, 10.56% (23,430 km²) of agricultural areas (non-buildable) are least suitable for urban development, 1.66% (12,771 km²) are forests (non-buildable), and 5.75% (3,686 km²) of these lands are considered unsuitable for urban development (perennial areas, non-buildable) but rather designated for agricultural use or strategic reserves hosting economic or tourist activity areas.This combination allows for handling complex spatial information and systematically evaluating various criteria, thus promoting optimal urban planning. Additionally, the process enabled visualization on maps of the area’s most suitable for urbanization and provided valuable insights to specialists for land use choices, including areas to develop, preserve, or protect.